Rhodamine-based fluorescence-magnetic resonance imaging agent as well as preparation method and application thereof

By combining Rhodamine BenQ's fluorescence-magnetic resonance imaging agent with multi-mode imaging technology, the problem of real-time non-destructive monitoring of the aging process of polymer materials has been solved, realizing visualized monitoring and performance evaluation of the aging process, and providing theoretical support for anti-aging strategies.

CN121379573APending Publication Date: 2026-01-23QUZHOU UNIV +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202511559774.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-10-29
Publication Date
2026-01-23

AI Technical Summary

Technical Problem

Existing technologies cannot perform real-time non-destructive monitoring and evaluation of the aging process of polymer materials, and it is difficult to effectively detect aging in the early stages.

Method used

Using Rhodamine B-lactam fluorescence-magnetic resonance imaging agent, pH-sensitive, free radical-responsive fluorescence-paramagnetic resonance imaging with the "open-close ring" mechanism of Rhodamine B-lactam is combined with fluorescence/electron paramagnetic resonance/magnetic resonance multi-mode imaging technology to visualize and diagnose the aging process of polymer materials.

Benefits of technology

This technology enables real-time visual monitoring of the aging process of polymer materials, improving the accuracy and sensitivity of detection, revealing the structural and performance changes during the aging process, and providing a theoretical basis for anti-aging strategies.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN121379573A_ABST
    Figure CN121379573A_ABST
Patent Text Reader

Abstract

The invention discloses a rhodamine-based fluorescence-magnetic resonance imaging agent as well as a preparation method and application thereof, and belongs to the technical field of materials science. The imaging agent is formed by coupling Fe3O4 (at) PAA nanoparticles as a core with a rhodamine-based fluorescence imaging group and a TEMPO-based paramagnetic resonance imaging group through a chemical reaction, and fluorescence imaging-electron paramagnetic resonance imaging-magnetic resonance imaging multi-mode combined imaging can be realized. The preparation method comprises the following steps: firstly, coupling a rhodamine-based fluorescence imaging group with Fe3O4 (at) PAA nanoparticles to obtain an intermediate product, then coupling the intermediate product with a TEMPO-based paramagnetic resonance imaging group, and carrying out dialysis and freeze drying to obtain a target imaging agent. During application, the imaging agent is mixed into the high polymer material, and the aging degradation process of the high polymer material is monitored through multi-mode signal change on the basis of a pH sensitive-free radical response mechanism of ring opening and closing of rhodamine lactam, so that real-time nondestructive monitoring and early-stage high-sensitivity diagnosis of aging of the high polymer material are realized.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of materials science and technology, specifically relating to a Rhodamine-based fluorescence-magnetic resonance imaging agent, its preparation method, and its application. Background Technology

[0002] Polymer materials, including rubber, plastics, fibers, coatings, adhesives, functional materials, and composite materials, have become indispensable substances in human society. Polymer materials have advantages such as abundant sources, ease of processing and molding, and high productivity.

[0003] Aging is the phenomenon in which the physicochemical and mechanical properties of polymer materials undergo irreversible deterioration during processing, storage, and application, due to physical factors such as heat, light, electricity, high-energy radiation, and mechanical stress, as well as chemical effects such as oxidation, thermo-oxidation, ozone, water, acids, alkalis, and enzymes, and the influence of biological fungi. These effects include yellowing, a decrease in relative molecular mass, cracking, and loss of luster. The impact strength, tensile strength, and elongation of the materials also decrease significantly, affecting their normal use, leading to the end of their service life and their disposal, resulting in resource waste, environmental pollution, and even potentially causing huge disasters and irreparable losses.

[0004] The aging of polymer materials is the result of a combination of factors, and there is no single method to prevent aging. Although various measures are currently employed, such as structural design or modification of polymer materials, addition of anti-aging additives, improvement of processing technology, and physical protection (e.g., thickening, coating, outer layer lamination), to improve and enhance the anti-aging performance of materials, the fundamental nature of polymer material aging remains unchanged. Therefore, dynamic assessment and real-time monitoring of the aging behavior of polymer materials, accurate evaluation of material stability and prediction of lifespan, and implementation of effective anti-aging measures are of paramount importance and are urgent problems to be solved in the polymer industry.

[0005] Many scholars have employed techniques such as scanning electron microscopy, optical microscopy, thermogravimetric analysis, energy-dispersive spectroscopy, and atomic force microscopy to characterize and evaluate the aging behavior of polymer materials. However, these techniques can only perform destructive sampling of materials and detect or evaluate the overall performance of polymer materials on a macroscopic scale. They cannot effectively monitor and evaluate the aging and performance change process in real time without damage, and they are difficult to effectively detect polymer materials in the early stages of aging. Therefore, visual imaging monitoring and diagnosis of the aging and degradation processes of various polymer materials has significant scientific theoretical value, good practical application value, and distinct leading or pioneering potential. It is also a key problem that urgently needs to be solved. Summary of the Invention

[0006] The purpose of this invention is to address the problem that existing technologies cannot effectively monitor and evaluate the aging and performance changes of polymer materials in real time without damage. This invention provides a rhodamine β-lactam fluorescence-magnetic resonance imaging agent, its preparation method, and its application. This imaging agent has a pH-sensitive, free radical-responsive fluorescence imaging-paramagnetic resonance imaging (EPRI)-magnetic resonance (MRI) multi-mode imaging function based on the "open-close ring" mechanism of rhodamine β-lactam, and can be used for visual imaging monitoring and diagnosis of the aging and degradation process of various polymer materials.

[0007] To solve the above-mentioned technical problems, one of the technical solutions adopted by the present invention is to provide a Rhodamine-based fluorescence-magnetic resonance imaging agent, which uses magnetite (Fe3O4@PAA) nanoparticles encapsulated with magnetic resonance imaging groups in polyacrylic acid as the core, and is formed by chemical reaction coupling with Rhodamine-based fluorescence imaging groups and TEMPO-based paramagnetic resonance imaging groups, having the general structural formula shown in formula (I): ; R1 and R2 are each independently selected from -CO(CH2CH2). n O-, -CO(CH2CH2) n NH-, -COCH2-, -SO-, -(CH2CH2) n O-, -(CH2CH2) n NH- or no group; R3 is selected from -O - -OH, alkoxy, aryloxy, amino, alkyl-substituted amino, aryl-substituted amino, R2-RhB or R1-TEMPO; x and y are natural numbers from 1 to 10000.

[0008] As a further description of the above technical solution: the average particle size of the Rhodamine Bioluminescent-Magnetic Resonance Imaging Agent is 1 nm to 0.1 mm, preferably 50 to 500 nm.

[0009] In a preferred embodiment of the present invention, the Rhodamine Bac fluorescent-magnetic resonance imaging agent has the structural formula shown in formula (II): .

[0010] In a preferred embodiment of the present invention, the Rhodamine Bac fluorescent-magnetic resonance imaging agent has the structural formula shown in formula (III): .

[0011] In a preferred embodiment of the present invention, the Rhodamine Bac fluorescent-magnetic resonance imaging agent has the structural formula shown in formula (IV): .

[0012] The second technical solution adopted in this invention is to provide a method for preparing the above-mentioned Rhodamine Bac fluorescent-magnetic resonance imaging agent, comprising the following steps: (1) Rhodamine Bimbo's fluorescent imaging group and polyacrylic acid-coated iron oxide (Fe3O4@PAA) nanoparticles were mixed evenly in a reaction solvent and coupled to form an intermediate compound Fe3O4@PAA-RhB. (2) The TEMPO-based paramagnetic resonance imaging group and the product Fe3O4@PAA-RhB obtained in step (1) are mixed in a reaction solvent to carry out a coupling reaction. After the coupling reaction is completed, the mixture is dialyzed and freeze-dried to obtain the Rhodamine fluorescent-magnetic resonance imaging agent Fe3O4@PAA-RhB / TEMPO shown in formula (I). The rhodamine-based fluorescent imaging group is selected from one of ethylenediamine-rhodamine B, hydroxymethyl-ethylenediamine-rhodamine B, and aminopropionyl-ethylenediamine-rhodamine B; the TEMPO-based paramagnetic resonance imaging group is selected from one of 4-hydroxymethyl-amino-2,2,6,6-tetramethylpiperidine nitride, 4-amino-2,2,6,6-tetramethylpiperidine nitride, and 4-aminopropionamido-2,2,6,6-tetramethylpiperidine nitride.

[0013] As a further description of the above technical solution: the reaction solvents in steps (1) and (2) are independently selected from water, dimethyl sulfoxide or N,N-dimethylformamide.

[0014] As a further description of the above technical solution: the dialysis in step (2) uses a dialysis bag with a molecular weight cutoff of 1000, and the dialysis water is changed every 2 hours during the dialysis process, and the total dialysis time is not less than 24 hours.

[0015] The third technical solution adopted in this invention is to provide the application of the above-mentioned Rhodamine fluorescein-magnetic resonance imaging agent, in which the Rhodamine fluorescein-magnetic resonance imaging agent is mixed into polymer materials as an additive or filler, and pH-sensitive-free radical responsive fluorescence imaging-paramagnetic resonance imaging-magnetic resonance multi-mode imaging based on the Rhodamine β-lactam "open-close ring" mechanism is used for the visualization imaging monitoring and diagnosis of the aging and degradation process of polymer materials.

[0016] As a further description of the above technical solution: the weight percentage of the Rhodamine-Mexico fluorescent-magnetic resonance imaging agent in the polymer material is 0.1-30%, preferably 1-10%.

[0017] To address the need for dynamic assessment and protection against aging in polymer materials during service, this invention employs commonly used imaging technologies (such as fluorescence imaging, electron paramagnetic resonance imaging, and magnetic resonance imaging). With signal enhancement from Rhodamine BenQ's fluorescence-magnetic resonance imaging agent, it performs multi-mode combined fluorescence / electron paramagnetic resonance / magnetic resonance imaging detection and monitoring of free radicals and acidic compounds generated during the aging process of polymer materials. This integrated imaging not only reflects the molecular reaction process and distribution information of the material at the molecular level but also reflects its anatomical morphology, obtaining more realistic and clear three-dimensional images of the material's local areas. This powerful combination of molecular functional imaging and morphological imaging, with complementary advantages, high sensitivity and resolution, will significantly improve the accuracy of material aging detection and monitoring.

[0018] Compared with the prior art, the beneficial effects of the present invention are: (1) The Rhodamine-Mingji fluorescence-magnetic resonance imaging agent of the present invention uses polyester polymers based on free radical degradation and acid hydrolysis mechanism as the research model. It uses fluorescence / electron paramagnetic resonance / magnetic resonance multi-mode combined imaging technology to conduct real-time visualization monitoring of the aging process of polymer materials, effectively and dynamically evaluates the aging process of polymer materials in service, further studies the method of real-time visualization monitoring of polymer material aging process and the influence mechanism on polymer material aging, reveals the change law of structure and performance of polyester and other polymer materials during aging process, provides theoretical basis and technical support for establishing anti-aging strategy of polymer materials, and provides new ideas for the research on aging mechanism and anti-aging of polymer materials.

[0019] (2) When polymer materials age during service, the production of acidic compounds increases through hydrolysis, which leads to the opening of the Rhodamine lactam spirocyclic structure (RhB-LEA) of the imaging agent and a significant enhancement of the red fluorescence imaging (FI) signal. At the same time, the nitroxide free radicals (-NO·) in the TEMPO structure of the imaging agent are easily quenched by reacting with the free radicals generated during the material aging process, resulting in a weakening of the electron paramagnetic imaging (EPRI) signal and magnetic resonance imaging (MRI) signal. This enables FI-EPRI-MRI multi-mode dynamic imaging detection, revealing the changes in structure and properties of polymer materials during aging and the influence mechanism of material aging, predicting the material performance failure time, and providing theoretical basis and technical support for establishing anti-aging strategies for polymer materials. Attached Figure Description

[0020] Figure 1 This is a fluorescence image obtained from PLA spline xenon lamp simulation of photothermal-oxidative accelerated aging monitoring.

[0021] Figure 2 This is a magnetic resonance imaging image obtained from PLA spline xenon lamp simulation of photothermal-oxidative accelerated aging monitoring.

[0022] Figure 3 This is the electron paramagnetic resonance spectrum of PLA composite spline xenon lamp simulated photothermal-oxidative accelerated aging monitoring. Detailed Implementation

[0023] The principles and features of the present invention are described below with reference to the accompanying drawings and specific embodiments. The embodiments given are only for explaining the present invention and do not constitute any limitation on the present invention. Any limited modifications made by any person within the scope of protection of the claims of the present invention are still within the scope of protection of the claims of the present invention.

[0024] Example 1: This example provides a Rhodamine B fluorescence-magnetic resonance imaging agent Fe3O4@PAA-RhB / TEMPO, which uses Fe3O4@PAA nanoparticles encapsulated with a magnetic resonance imaging group in polyacrylic acid as the core, and is formed by chemically coupling with an ethylenediamine-modified Rhodamine B fluorescence imaging group and a 4-amino-2,2,6,6-tetramethylpiperidine nitride (4-NH2-TEMPO) paramagnetic resonance imaging group, and has the structural formula shown in formula (II) (R1 and R2 are without groups, R3 is -OH): .

[0025] Its preparation process includes the following steps: (1) Weigh 500 mg of polyacrylic acid-coated Fe3O4@PAA nanoparticles (carboxyl content 0.0125 mmol / mg), 1.79 g of 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide hydrochloride (EDC, 9.375 mmol) and 1.07 g of N-hydroxysuccinimide (NHS, 9.375 mmol, intermediate stabilizer) and add them to a 150 mL Erlenmeyer flask. Add 10 mL of dimethyl sulfoxide (DMSO, reaction solvent) and sonicate until uniformly dispersed (a dark brown liquid). Place the Erlenmeyer flask in a constant temperature shaker and activate the reaction at 37 ℃ and 120 rpm for 4 h. Then add 1.5 g of ethylenediamine-rhodamine B (EDA-RhB, 3.125 mmol), sonicate until uniformly dispersed, and react at room temperature for 96 h to obtain Fe3O4@PAA-RhB reaction solution. (2) Add 0.5 g of 4-amino-2,2,6,6-tetramethylpiperidine N-oxide (4-NH2-TEMPO, 3.125 mmol) and 0.5 mL of triethylamine (pH adjuster) to the Fe3O4@PAA-RhB reaction solution in step (1), and add 20 mL of DMSO. Dissolve the solution by sonication until homogeneous (resulting in a reddish-brown solution). Under conditions of darkness, 37 ℃, and 120 rpm, shake the reaction solution for 48 h. After the reaction is complete, transfer the reaction solution to a dialysis bag with a molecular cutoff of 1000 and dialyze it with deionized water for 24 h (changing the water every 2 h during this period). After dialysis, freeze-dry the liquid in the dialysis bag to obtain a reddish-brown solid powder, which is the Rhodamine Biotech fluorescence-magnetic resonance imaging agent Fe3O4@PAA-RhB / TEMPO, with a yield of 75%. Its hydrated particle size is 137.4 nm, and its Zeta charge is -2.43 mV. The particle size is uniform and evenly distributed, providing stable dispersion and imaging basis.

[0026] Preparation of PLA composite specimens: Weigh 198 g of polylactic acid (PLA, Mn, 2×10⁻⁶ g) 5 2 g of the Rhodamine Benzyne fluorescent-magnetic resonance imaging agent Fe3O4@PAA-RhB / TEMPO prepared in this example were added to 800 mL of dichloromethane. The mixture was stirred and shaken to fully dissolve and disperse it evenly. The mixture was then spread into a film on a glass plate. After the dichloromethane evaporated naturally, the material was crushed into powder using a multi-functional pulverizer and mixed evenly again. The blended composite material was then injection molded using a micro injection molding machine. The melt temperature was set to 175 ℃, the mold closing time was 2 s, and the injection time was 12 s to prepare PLA composite strips containing 1% Fe3O4@PAA-RhB / TEMPO.

[0027] Aging monitoring experiment: PLA samples and PLA composite samples were placed under a xenon lamp to simulate a photothermal-oxidative accelerated aging environment. Weight, molecular weight, imaging signals (fluorescence imaging FI, magnetic resonance imaging MRI, electron paramagnetic resonance imaging EPRI), and mechanical property data of the samples were collected periodically. Changes in thermal properties were also recorded. The results are as follows: Changes in basic properties of the specimens: With prolonged aging time, the weight loss rate of the specimens gradually increased, the molecular weight (number-average molecular weight Mn, weight-average molecular weight Mw) gradually decreased, the mechanical properties gradually declined, the glass transition temperature and melting temperature decreased, and the crystallization temperature changed slightly. Specifically, after 30 days of aging, the weight loss rate of the specimens was approximately 2%; the Mn loss was 89702 Da (loss rate 48.67%); the Mw loss was 93091 Da (loss rate 42.84%); and the tensile strength of the specimens decreased from the initial 45.61 MPa to 10.48 MPa.

[0028] Fluorescence imaging (FI) monitoring results: Compared with pure PLA samples, the addition of an imaging agent enables fluorescence imaging monitoring of material aging. Since this imaging agent uses a rhodamine lactam structure as the FI group, it reflects the molecular mechanism of the aging process. During the aging process, the fluorescence imaging signal intensity of the PLA composite sample containing the imaging agent shows a trend of "first increasing and then decreasing," as shown below. Figure 1 As shown, when 1% imaging agent Fe3O4@PAA-RhB / TEMPO was added, the fluorescence imaging signal intensity increased most significantly after 36 hours of aging, reaching 22.1 times the initial fluorescence imaging signal intensity; after 10–15 days of aging, the fluorescence imaging signal intensity was 15 times the initial signal intensity; and after 30 days of aging, the fluorescence imaging signal intensity remained 4.8 times the initial signal intensity. In the xenon lamp-simulated photothermal-oxidative accelerated aging process, the addition of the imaging agent to PLA resulted in highly sensitive fluorescence imaging in the early stages of aging, with the fluorescence imaging signal intensity reaching its peak in a short time, exhibiting a high enhancement factor and good contrast. This indicates that the imaging agent has advantages in monitoring during the early stages of aging. The enhanced fluorescence imaging signal intensity in the early stages is mainly due to the production of acidic byproducts during PLA aging, leading to the ring-opening of rhodamine lactone and the release of strong fluorescence. The decreased fluorescence imaging signal intensity in the later stages is primarily due to the limited photostability of rhodamine-based fluorescent imaging diagnostic agents. In simulated photothermal-oxidative accelerated aging, prolonged exposure to xenon lamp irradiation at high temperatures and under severe aging conditions resulted in a photobleaching effect, leading to a gradual decrease in fluorescence imaging signal intensity. Overall, this imaging agent is particularly suitable for early diagnosis in monitoring the photothermal-oxidative accelerated aging of PLA.

[0029] Magnetic resonance imaging (MRI) monitoring results: This imaging agent uses Fe3O4 as the T2-weighted imaging group and TEMPO as the T1-weighted imaging group for MRI to reflect the material's structural morphology; during monitoring, the MRI signal intensity gradually weakened with increasing aging time, such as... Figure 2 As shown, pure PLA samples, due to their weak inherent magnetic resonance imaging (MRI) capabilities, could not produce clear MRI images. However, PLA composite samples with 1% Fe3O4@PAA-RhB / TEMPO as the imaging agent exhibited better MRI results, with clear structures and complete images. With prolonged aging time, the MRI signal intensity showed a weakening trend, which may be due to the loss of Fe3O4 nanoparticles in the imaging agent during the aging process in a thermo-oxidative environment. After 30 days of aging, the MRI intensity decreased by a factor of 2.0 compared to the initial intensity. This indicates that in PLA xenon lamp-simulated photothermal-oxidative accelerated aging, the addition of 1% Fe3O4@PAA-RhB / TEMPO as the imaging agent resulted in good MRI performance.

[0030] Its electron paramagnetic resonance spectrum ( Figure 3The image shows the spectral lines of the triplet hyperfine structure of nitrile-oxygen radicals. With increasing aging time, the intensity of the electron paramagnetic resonance (EPR) spectrum generally showed a gradual decreasing trend. After 15 days of aging, the peak intensity (3419.7 G, intensity value 0.83106) was approximately 3.17 times weaker than before aging (3419.1 G, intensity value 2.63548). This indicates that the diagnostic agent Fe3O4@PAA-RhB / TEMPO can effectively capture free radicals generated during PLA aging and exhibits good free radical response capability.

[0031] Example 2: This example provides a Rhodamine B fluorescence-magnetic resonance imaging agent Fe3O4@PAA-RhB / TEMPO, which uses polyacrylic acid-encapsulated iron(III) oxide (Fe3O4@PAA) nanoparticles as the core, and is formed by chemically coupling with hydroxymethylethylenediamine-modified Rhodamine B fluorescence imaging group and 4-hydroxymethylamino-2,2,6,6-tetramethylpiperidine nitride (4-NOHCH3-TEMPO) paramagnetic resonance imaging group, having the structural formula shown in formula (III) (R1, R2 are -CH2O-, R3 is -OH): .

[0032] Its preparation process includes the following steps: (1) Weigh 500 mg of polyacrylic acid-coated Fe3O4@PAA nanoparticles (carboxyl content 0.0125 mmol / mg), 1.79 g of 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide hydrochloride (EDC, 9.375 mmol) and 1.07 g of N-hydroxysuccinimide (NHS, 9.375 mmol) and add them to a 150 mL Erlenmeyer flask. Add 10 mL of DMSO and sonicate until the mixture is evenly dispersed (a dark brown liquid). Place the Erlenmeyer flask in a constant temperature shaker and activate the reaction at 37 °C and 120 rpm for 4 h. Then add 1.7 g of hydroxymethyl-ethylenediamine-rhodamine B (HOCH2NH-EDA-RhB, 3.125 mmol), sonicate until evenly dispersed, and react at room temperature for 96 h to obtain Fe3O4@PAA-RhB reaction solution. (2) Add 0.5 g of 4-hydroxymethyl-amino-2,2,6,6-tetramethylpiperidine nitride (4-HOCH2NH-TEMPO, 3.125 mmol) and 0.5 mL of triethylamine to the Fe3O4@PAA-RhB reaction solution in step (1), and add 20 mL of DMSO. Dissolve the solution by sonication until homogeneous (resulting in a reddish-brown solution). Under conditions of darkness, 37 °C, and 120 rpm, shake the reaction solution for 48 h. After the reaction is complete, transfer the reaction solution to a dialysis bag with a molecular cutoff of 1000 and dialyze it with deionized water for 24 h (changing the water every 2 h). After dialysis, freeze-dry the liquid in the dialysis bag to obtain a reddish-brown solid powder, which is the Rhodamine Biotech fluorescent-magnetic resonance imaging agent Fe3O4@PAA-RhB / TEMPO, with a yield of 70%.

[0033] Preparation of PTMC composite specimens: Weigh 192 g of polytrimethylene carbonate (PTMC, Mn, 3×10⁻⁶). 5 8 g of the Rhodamine Benzyne fluorescent-magnetic resonance imaging agent Fe3O4@PAA-RhB / TEMPO prepared in this embodiment was added to 800 mL of dichloromethane. The mixture was stirred and vibrated until fully dissolved and evenly dispersed. The solution was then spread onto a glass plate. After the dichloromethane evaporated naturally, the material was crushed into powder using a multi-functional pulverizer and mixed again until homogeneous. The blended composite material was then injection molded using a micro-injection molding machine. The melt temperature was set to 200 °C, the mold closing time to 2 s, and the injection molding time to 12 s, to prepare a PTMC composite strip containing 4% Fe3O4@PAA-RhB / TEMPO. During the aging process, this strip can be monitored using multi-mode monitoring via fluorescence imaging, magnetic resonance imaging, and electron paramagnetic resonance imaging, enabling visual tracking of the aging process.

[0034] Example 3: This example provides a Rhodamine B fluorescence-magnetic resonance imaging agent Fe3O4@PAA-RhB / TEMPO, which uses polyacrylic acid-encapsulated iron(III) oxide (Fe3O4@PAA) nanoparticles as the core, and is formed by chemically coupling with an aminopropamidyl-ethylenediamine modified Rhodamine B fluorescence imaging group and a 4-aminopropamidyl-2,2,6,6-tetramethylpiperidine nitride paramagnetic resonance imaging group, having the structural formula shown in formula (IV) (R1, R2 are -COCH2CH2NH-, R3 is -OH): .

[0035] Its preparation process includes the following steps: (1) Weigh 500 mg of polyacrylic acid-coated Fe3O4@PAA nanoparticles (carboxyl content 0.0125 mmol / mg), 1.79 g of 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide hydrochloride (EDC, 9.375 mmol) and 1.07 g of N-hydroxysuccinimide (NHS, 9.375 mmol) and add them to a 150 mL Erlenmeyer flask. Add 10 mL of DMSO and sonicate until the mixture is evenly dispersed (a dark brown liquid). Place the Erlenmeyer flask in a constant temperature shaker and activate the reaction at 37 °C and 120 rpm for 4 h. Then add 1.8 g of aminopropionamido-ethylenediamine-rhodamine B (H2NCH2CH2CO-EDA-RhB, 3.125 mmol), sonicate until evenly dispersed, and react at room temperature for 96 h to obtain Fe3O4@PAA-RhB reaction solution. (2) Add 0.8 g of 4-aminopropionamido-2,2,6,6-tetramethylpiperidine nitride (4-H2NCH2CH2CONH-TEMPO, 3.125 mmol) and 0.5 mL of triethylamine to the Fe3O4@PAA-RhB reaction solution in step (1), and add 20 mL of DMSO. Dissolve the solution by sonication until homogeneous (resulting in a reddish-brown solution). Under conditions of darkness, 37 °C, and 120 rpm, shake the reaction solution for 48 h. After the reaction is complete, transfer the reaction solution to a dialysis bag with a molecular cutoff of 1000 and dialyze it with deionized water for 24 h (changing the water every 2 h during this period). After dialysis, freeze-dry the liquid in the dialysis bag to obtain a reddish-brown solid powder, which is the Rhodamine Biotech fluorescent-magnetic resonance imaging agent Fe3O4@PAA-RhB / TEMPO, with a yield of 65%.

[0036] Preparation of PET composite specimens: Weigh 180 g of polyethylene terephthalate (PET, Mn, 2-3×10⁻⁶). 4 20 g of the Rhodamine Benzyne fluorescent-magnetic resonance imaging agent Fe3O4@PAA-RhB / TEMPO prepared in this example was added to 800 mL of dichloromethane. The mixture was stirred and vibrated until fully dissolved and evenly dispersed. The solution was then spread onto a glass plate. After the dichloromethane evaporated naturally, the material was crushed into powder using a multi-functional pulverizer and mixed again until homogeneous. The blended composite material was then injection molded using a micro-injection molding machine. The melt temperature was set to 280 °C, the mold closing time to 2 s, and the injection molding time to 12 s, to prepare a PET composite strip containing 10% Fe3O4@PAA-RhB / TEMPO. During the aging process, this strip can be monitored using multi-mode monitoring via fluorescence imaging, magnetic resonance imaging, and electron paramagnetic resonance imaging, enabling visual tracking of the aging process.

[0037] The imaging agent of this invention uses a rhodamine lactam structure as the fluorescence imaging (FI) group, Fe3O4 as the MRI group, and TEMPO free radical as the electron paramagnetic resonance imaging (EPRI) group. Fe3O4 is used for T2-weighted imaging in magnetic resonance imaging (MRI), and TEMPO is used for weighted T1 imaging in MRI. FI is used for mechanistic imaging, MRI for structural imaging, and EPRI for free radical response imaging. The polymer composite material containing the imaging agent Fe3O4@PAA-RhB / TEMPO of this invention can effectively track the aging process of PLA in real time through multi-mode combined monitoring of fluorescence imaging, magnetic resonance imaging, and electron paramagnetic resonance imaging, achieving both early sensitive diagnosis and full-process dynamic assessment.

[0038] The above embodiments are only used to illustrate the technical solutions of the present invention, and are not intended to limit them; those skilled in the art should understand that modifications can still be made to the technical solutions described in the foregoing embodiments, or equivalent substitutions can be made to some of the technical features; and these modifications or substitutions will not cause the essence of the corresponding technical solutions to deviate from the protection scope of the present invention.

Claims

1. A Rhodaminebenz fluorescence-magnetic resonance imaging agent, characterized in that, The imaging agent is formed by chemically coupling iron oxide nanoparticles encapsulated in polyacrylic acid with magnetic resonance imaging groups to Rhodamine Bacillus fluorescent imaging groups and TEMPO paramagnetic resonance imaging groups, and has the general structural formula shown in formula (I): ; R1 and R2 are each independently selected from -CO(CH2CH2). n O-, -CO(CH2CH2) n NH-, -COCH2-, -SO-, -(CH2CH2) n O-, -(CH2CH2) n NH- or no group; R3 is selected from -O - -OH, alkoxy, aryloxy, amino, alkyl-substituted amino, aryl-substituted amino, R2-RhB or R1-TEMPO; x and y are natural numbers from 1 to 10000.

2. The Rhodamine Bright Crystal Fluorescence-Magnetic Resonance Imaging Agent according to claim 1, characterized in that: The average particle size of the Rhodamine Bioluminescent Magnetic Resonance Imaging Agent is 1 nm to 0.1 mm.

3. The Rhodamine Bac fluorescent-magnetic resonance imaging agent according to claim 2, characterized in that, The Rhodamine Bac fluorescent-magnetic resonance imaging agent has the structural formula shown in formula (II): 。 4. The Rhodamine Bac fluorescent-magnetic resonance imaging agent according to claim 2, characterized in that, The Rhodamine Bac fluorescent-magnetic resonance imaging agent has the structural formula shown in formula (III): 。 5. The Rhodamine Bac fluorescent-magnetic resonance imaging agent according to claim 2, characterized in that, The Rhodamine Bac fluorescent-magnetic resonance imaging agent has the structural formula shown in formula (IV): 。 6. The method for preparing the Rhodamine Bac fluorescent-magnetic resonance imaging agent according to any one of claims 1 to 5, characterized in that, Includes the following steps: (1) Rhodamine Bimbo's fluorescent imaging group and polyacrylic acid-coated iron oxide nanoparticles were mixed evenly in a reaction solvent and coupled to form an intermediate compound Fe3O4@PAA-RhB; (2) The TEMPO-based paramagnetic resonance imaging group and the product Fe3O4@PAA-RhB obtained in step (1) are mixed in a reaction solvent to carry out a coupling reaction. After the coupling reaction is completed, the mixture is dialyzed and freeze-dried to obtain the Rhodamine fluorescent-magnetic resonance imaging agent Fe3O4@PAA-RhB / TEMPO shown in formula (I). The rhodamine-based fluorescent imaging group is selected from one of ethylenediamine-rhodamine B, hydroxymethyl-ethylenediamine-rhodamine B, and aminopropionyl-ethylenediamine-rhodamine B; the TEMPO-based paramagnetic resonance imaging group is selected from one of 4-hydroxymethyl-amino-2,2,6,6-tetramethylpiperidine nitride, 4-amino-2,2,6,6-tetramethylpiperidine nitride, and 4-aminopropionamido-2,2,6,6-tetramethylpiperidine nitride.

7. The preparation method according to claim 6, characterized in that: The reaction solvents used in steps (1) and (2) are independently selected from water, dimethyl sulfoxide, or N,N-dimethylformamide.

8. The preparation method according to claim 6, characterized in that: The dialysis described in step (2) uses a dialysis bag with a molecular weight cutoff of 1000. The dialysis water is changed every 2 hours during the dialysis process, and the total dialysis time is not less than 24 hours.

9. The application of the Rhodamine Bac fluorescent-magnetic resonance imaging agent according to any one of claims 1 to 5, characterized in that: Rhodamine B-lactam fluorescence-magnetic resonance imaging agent is mixed into polymer materials as an additive or filler. Through pH-sensitive, free radical-responsive fluorescence imaging-paramagnetic resonance imaging-magnetic resonance multi-mode imaging based on the "open-close ring" mechanism of rhodamine B-lactam, it can be used for the visualization imaging monitoring and diagnosis of the aging and degradation process of polymer materials.

10. The application according to claim 9, characterized in that: The Rhodamine Bac fluorescent-magnetic resonance imaging agent has a weight percentage of 0.1% to 30% in the polymer material.